2016
DOI: 10.5713/ajas.16.0218
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different ratios and storage periods of liquid brewer’s yeast mixed with cassava pulp on chemical composition, fermentation quality and in vitro ruminal fermentation

Abstract: ObjectiveThis study aims to evaluate the chemical composition, fermentation quality and in vitro ruminal fermentation of various ratios and storage periods of liquid brewer’s yeast (LBY) mixed with cassava pulp (CVP).MethodsFour mixtures of fresh LBY and CVP were made (LBY0, LBY10, LBY20, and LBY30 for LBY:CVP at 0:100, 10:90, 20:80, and 30:70, respectively) on a fresh matter basis, in 500 g in plastic bags and stored at 30 to 32°C. After storage, the bags were opened weekly from weeks 0 to 4. Fermentation qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 16 publications
7
14
0
Order By: Relevance
“…The chemical composition of CSYW in this experiment had lower OM, NDF, and ADF content than the compositions within the study conducted by Sommai et al [5]. These variations may be a result of different materials, growing locations, and plant factory processing [23]. However, the OM, NDF, and ADF contents in CSYW were similar to those of the report of Chuelong et al [24], with 845, 243, and 113 g/kg DM, respectively.…”
Section: Chemical Compositionsupporting
confidence: 75%
See 1 more Smart Citation
“…The chemical composition of CSYW in this experiment had lower OM, NDF, and ADF content than the compositions within the study conducted by Sommai et al [5]. These variations may be a result of different materials, growing locations, and plant factory processing [23]. However, the OM, NDF, and ADF contents in CSYW were similar to those of the report of Chuelong et al [24], with 845, 243, and 113 g/kg DM, respectively.…”
Section: Chemical Compositionsupporting
confidence: 75%
“…According to Menke and Steingass [17], artificial saliva preparations contained distilled water (1095 mL), a micro mineral mixture (0. 23 4.0 g/L). The artificial saliva was then combined with rumen fluid (660 mL) in a non-oxygen atmosphere.…”
Section: Ruminal Fluid Donors and Substrates Of Inoculummentioning
confidence: 96%
“…The main effect of BSY level (%) and ED (week) on fresh silage DM and chemical composition of substitute other protein sources from the diet of animals. The Metabolizable energy content of FBSY from the present study was about 12.2 MJ/kg DM and thus goes comparable with an earlier report byKamphayae et al (2017). Brewery spent grain in the present study had a DM content of 256 g/kg which was more or less in accordance with earlier values 200-250 g/kg reported byKarlović et al (2020), but lower than the value 292 g reported by Senthilkumar et al (2010), and higher than the value 242 g/kg reported by Getu et al (2022).…”
supporting
confidence: 92%
“…The IVOMD and EME of silage material in the present study were in the range of 607-689 g/kg DM, and 9.7-11.0 MJ/kg DM, respectively with relatively higher IVOMD and EME values in the present study being reported for 20% of BSY level and that ensiled for 4 to 6 weeks. In a related study by Kamphayae et al (2017) the inclusion of BSY level in cassava pulp by up to 30% substantially improved IVOMD and EME of silage material within 4 weeks from initial date of ensiling period.…”
Section: Fermentative Characteristics Of Bsy-based Silagementioning
confidence: 89%
“…Currently, there is an increasing surplus of cassava ( Manihot esculenta Crantz) pulp that is available year round for animal feed because Thai cassava starch is an industrial by-product. Cassava contains abundant digestible starch and fiber, and its nutritive value makes it suitable as an alternative energy feed source to rice straw [ 7 9 ]. The use of high-energy-dense diets, which typically contain high levels of non-fiber carbohydrate (NFC) to improve digestibility, reduces enteric methane intensity in beef cattle because the degradation of NFC in the rumen affects the activity of methanogenic archaea and other microbes leading to suppressed methane production.…”
Section: Introductionmentioning
confidence: 99%